(untitled) (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2019)
The objectives of this study are as follows: (1) Describe the steps of the scientific approach and NHT models assisted by visual media in class IV students of SD Negeri 2 Padas Semester II Theme 6 Academic Year 2018/2019 and (2) This study is to find out the increase Science learning theme 6 sub-theme 2 learning 1 can be pursued through the scientific approach and Numbered Head Together (NHT) learning model assisted by visual media in class IV students of SD Negeri 2 Padas Semester II Theme 6 Academic Year 2018/2019. This research method uses the type of Classroom Action Research (CAR), and uses data collection techniques in the form of formative tests, observation sheets and interviews. The data collected in this CAR research is descriptive qualitative and quantitative descriptive. The results showed that through the Scientific approach and Numbered Head Together (NHT) learning model assisted by Visual media can improve learning outcomes in science thematically. Can be seen in the pre-cycle number of students who completed the KKM IPA ? 68 were 8 students (40%), cycle 1 increased to 10 students (50%), cycle 2 increased to 15 students (75%) had reached KKM which have been set. It can be concluded that through the Scientific approach and Numbered Head Together (NHT) learning model assisted by visual media can improve science learning outcomes in thematic fourth grade students of Padas 2 Elementary School.